2020
DOI: 10.1093/ons/opaa422
|View full text |Cite
|
Sign up to set email alerts
|

Petrosal Vein Involvement in Neurovascular Conflict in Trigeminal Neuralgia: Surgical Technique and Clinical Outcomes

Abstract: BACKGROUND Contact of the main stem of the petrosal vein (PV) to the nerve root is a rare cause of trigeminal neuralgia (TGN). The implication of the PV in relation with neurovascular contact (NVC) is not fully understood. OBJECTIVE To assess the operative procedures in microvascular decompression (MVD) in patients with PV involvement in the long-term. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The usefulness of cutting the TPV during MVD, including our report, 9,28 has been investigated, but maintaining the venous return of the SPV is unclear. We here propose a hypothesis for the safe sacrifice of the SPV based on the TPV's ability to provide compensatory collateral flow pathways.…”
Section: Discussionmentioning
confidence: 94%
“…The usefulness of cutting the TPV during MVD, including our report, 9,28 has been investigated, but maintaining the venous return of the SPV is unclear. We here propose a hypothesis for the safe sacrifice of the SPV based on the TPV's ability to provide compensatory collateral flow pathways.…”
Section: Discussionmentioning
confidence: 94%
“…Shorter vein cannot be easily stretched, while forced displacement or direct coagulation may damage venous refluxes and result in severe complications and even death. [23][24][25] The vein was only slightly separated in the first operation. When there is no pain relief, we totally separated it during re-do operation.…”
Section: Discussionmentioning
confidence: 99%
“…MVD can be used for patients whose pain is not relieved after interventional embolization. A study by Fukushima et al found that separating the petrosal vein from the nerve root contributes to pain relief in patients with petrosal vein conflict, regardless of the accompanying artery [ 30 ]. Different from what is seen in primary TN surgery, the SPV often exhibits venous lake changes; after embolization, vein thrombosis forms and the texture becomes hard, making the SPV difficult to move and significantly increasing the difficulty of the operation.…”
Section: Discussionmentioning
confidence: 99%